Three years survival rate of epithelial ovarian cancer patients in Dr. Kariadi Hospital, Semarang, Central Java - Indah Nur Damayanti; Indra Yulianti; Etty Hary Kusumastuti (Majalah Obstetri dan Ginekologi, 2016)
Objectives: to determine the association between prognostic factors of ovarian cancer with a 3-years survival rate of epithelial ovarian cancer patients.Material and Method:  Retrospective cohort study was conducted in 90 patients (during 2012) at Dr.Kariadi General Hospital. Kaplan meier, Log rank and Cox regression were used to analyse survival rate and prognostic factors that influence the disease.Result: Overall 3-years survival rate of epithelial ovarian cancer patients were 58.5% (Kaplan meier). Three-years survival rates were 89.3%, 44,4%, and 35.1% for patients in stage I, stage II, and stage III, respectively, and no patient survive up to 3 years in stage IV. Prognostic factors that associated with 3-years survival rate were stage of the disease, ascites, residual tumor, and type of histopathology {p<0,001; p=0,001; p=0,004; p=0,041, respectively (Log rank test)}, whereas age and size of tumor were not associated. After using multivariate analysis (Cox regression) only stage of the disease was associated with 3-years survival rate of epithelial ovarian cancer patients.Conclusion: There were an association between stage of the disease, ascites, residual tumor, type of histopathology, and 3-years survival rate of epithelial ovarian cancer patients. Stage of the disease was a prognostic factor that most influence 3-years survival rate of epithelial ovarian cancer patiens in this study.